Analisis Implementasi Kebijakan Penyetaraan Jabatan Fungsional Pengelola Pengadaan Barang dan Jasa Di Lingkungan Kemendikbudristek - Mutiara Azhari, Puti; Franky; Mega Utama, Zahera (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
This research aims to look at the implementation of the policy of changing Administrative Positions to Functional Positions of Goods and Services Procurement Managers in the Ministry of Education and Culture and Research and Technology and to analyze the impact of changes in the policy of equalizing Administrative Positions to Functional Positions of Goods and Services Procurement Managers in the Ministry of Education and Culture and Research and Technology on the Human Resource Management Function. This is motivated by the president's policy regarding the equalization of administrative positions to functional positions. This research design uses qualitative methods. Data collection techniques in this research used interviews, observation and documentation. The subjects in this research are the Substance Coordinator of Mentoring, Consultation and/Bintek PBJ, the Substance Coordinator of Human Resources and Institutional Development, the Functional Position of Goods/Services Procurement Manager, and the Human Resources Bureau of the Secretary General of the Ministry of Education and Culture. The research results show that functional officials who are affected by the position equalization policy are in practice entrusted with the role of coordinator or sub-coordinator, which in other words, they are still given authority and responsibility in certain fields as attached to their previous position. So that "structural sense functional officials" emerge. This condition increases the burden on officials affected by equalization. On the one hand, the person concerned must follow the work climate of a functional position which is based on individual performance with proof of collecting credit scores, on the other hand he is given the burdens, responsibilities and roles as in the structural position previously held.